Female University Students Working in the Sex Trade: A Narrative Analysis - Sinacore, Ada L.; Jaghori, Beheshta; Rezazadeh, Shohreh M. (Canadian Journal of Counselling and Psychotherapy, 2014)
This research examined the narratives of 4 female Canadian university students working in the sex trade. Factors that resulted in students being both receptive to sex work and sustained by it, as well as variables that finally led to their exit from sex work, were identified. The study highlights the relevance of this topic to the field of counselling psychology. The benefits and consequences of working in the sex industry, as well as educational, psychosocial, and career implications, are discussed.